Activity-Dependent Pre-miR-134 Dendritic Localization Is Required for Hippocampal Neuron Dendritogenesis - Zampa, Federico; Bicker, Silvia; Schratt, Gerhard (Frontiers in Molecular Neuroscience, 2018)
microRNAs (miRNAs) have emerged as critical regulators of neuronal dendrite development. Specific precursor (pre-)miRNAs are actively transported to dendrites, but whether this process is regulated by neuronal activity and involved in activity-dependent dendritogenesis is unknown. Here we show that BDNF, a neurotrophin that is released in response to increased neuronal activity, promotes dendritic accumulation of pre-miR-134. Dendritic accumulation, but not transcription of pre-miR-134, is abrogated by treatment of neurons with the NMDA receptor antagonist APV. Furthermore, APV interferes with BDNF-mediated repression of the known miR-134 target Pumilio 2 (Pum2) in a miR-134 binding site-specific manner. At the functional level, both APV treatment and knockdown of the pre-miR-134 transport protein DHX36 antagonise BDNF-induced dendritogenesis. These effects are likely mediated by reduced dendritic miR-134 activity, since both transfection of a synthetic miR-134 duplex or of a dendritically targeted miR-134-181a chimera rescues BDNF-dependent dendritogenesis in the presence of APV. In conclusion, we have identified a novel NMDA receptor-dependent mechanism involved in the activity-dependent control of miRNA function during neuronal development.